2022
DOI: 10.1186/s12887-022-03527-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pulmonary fissure completeness on major outcomes in children after video-assisted thoracoscopic congenital lung malformation lobectomy

Abstract: We performed a single-centre retrospective analysis using data from databases that were prospectively maintained in our centre between January 2019 and September 2021. Patients were divided into two groups based on the degree of pulmonary fissure completeness (PFC), using the fissure development scoring system. Patients with grades 2 or 3 PFC were considered to have incomplete pulmonary fissures and were included in Group A, and patients with grades 0 and 1 were considered to have complete pulmonary fissures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Patients that had incomplete interlobar ssures and went through a videoassisted thoracoscopic lobectomy had increased overall post-operative morbidity rate and were greatly associated with pneumothorax, pleural effusion, and atelectasis [20]. Huang et al [13] reported that incomplete pulmonary ssures were greatly associated with post-operative complications such as prolonged length of chest tube drainage and hospital stay. Koster and Slebos [19] demonstrated that the possibility of collateral ventilation is high with incomplete pulmonary ssures.…”
Section: Discussionmentioning
confidence: 99%
“…Patients that had incomplete interlobar ssures and went through a videoassisted thoracoscopic lobectomy had increased overall post-operative morbidity rate and were greatly associated with pneumothorax, pleural effusion, and atelectasis [20]. Huang et al [13] reported that incomplete pulmonary ssures were greatly associated with post-operative complications such as prolonged length of chest tube drainage and hospital stay. Koster and Slebos [19] demonstrated that the possibility of collateral ventilation is high with incomplete pulmonary ssures.…”
Section: Discussionmentioning
confidence: 99%